The oxidative-stress level determine patient’s outcomes with a severe head injury at Sanglah General Hospital, Denpasar, Indonesia - I Made Bagus Wirawan; I Nyoman Golden; I Wayan Niryana (Intisari Sains Medis, 2019)
Background: In secondary brain injury, oxidative stress will occur due to a balance disorder between pro-oxidants with antioxidants. The antioxidant activity that is often used to assess oxidative stress, such as malondialdehyde (MDA), is superoxide dismutase (SOD) and glutathione peroxidase (GPx). This study aims to evaluate the level of oxidative stress, reflected by the MDA serum level and SOD level to determine the outcomes of patients with severe head injury.Method: A cross-sectional analytic study was conducted among 40 patients with severe head injury within 24 hours post-trauma at Emergency Ward, Surgery Department, Sanglah General Hospital Denpasar from January - June 2017. MDA and SOD levels were assessed using ELISA at Clinical Pathology Laboratory, Sanglah General Hospital. Data were analyzed using SPSS ver. 16 software. Results: This study found significant differences on elevated MDA levels (p-value < 0.05) in patients who died or had a persistent vegetative state, patients with severe disability and those with a good recovery/moderate disability. The statistical analysis also found a significant difference in MDA serum levels among patient with severe disability and patients with a good recovery/moderate disability (P=0,028). Meanwhile, there was no significant correlation between SOD serum levels and patients outcome (P>0.05).Conclusion: Increased MDA serum levels is a significant factor in predicting outcomes of patients with severe head injury.